Pest in the nest - Gough, Julian; Field, Jim 1980- (San Diego, CA Silver Dolphin, 2018)
Between his friend Bear's snoring and annoying neighbors, Rabbit cannot find any peace and quiet, but perhaps Bear can give Rabbit a new perspective.
112406
Keywords: Noise -- Juvenile fiction; Adaptability (Psychology) -- Juvenile fiction; Rabbits -- Juvenile fiction; Bears -- Juvenile fiction; Woodpeckers -- Juvenile fiction; Humorous stories; Social Issues -- Friendship; illustrated books; Juvenile works; Fiction; Humorous fiction